HP0020 Pain treatment of the rheumatic disorders with electric therapy. (1st June 2001) - Basic, NK; Basic, M; Masatovic, D
Abstract : Pain relief is one of the most important assignments of physical therapy (PT) and for that purpose different procedures have been used. Their advantage is that they have no side effects, which is very important for rheumatic patients, who are forced to take NSAIDs for a very long period. The aim of this work was to investigate effects of different electric procedures on pain and joint swelling of rheumatic patients. Material and methods: The investigation was conducted on 40 patients with knee osteoarthritis and rheumatoid arthritis. Every knee was treated with different electric procedure. Mean age of patients was 54.6 years (SD 8.9), and mean duration of the illness was 12.1 years (SD 8.7). Interferrent, modulated and galvanic currents have been used. Treatment lasted for four weeks and in that period every patient received 20 therapies. Pain degree has been evaluated according to analogue visual scale -VAS (0–100) before and after the treatment. At the end of the treatment patients and physicians have given their evaluation of the PT effect separately with grades from 1 to 5 (1- poor effect and 5 – excellent effect). Results: All three currents had good analgesic effect and there was a statistically significant difference in the pain evaluation before and after the application of all electric procedures (p < 0.001). By the application of galvanic current knee pain was evaluated as 80.25 before the therapy and it was reduced to 33 after PT. Modulated currents application led to pain reduction from 82 to 33, and interferrent currents application from 88.5 to 37.5. However there was no significant difference in analgesic effect between the different procedures. As far as the joint swelling is concerned, it has been reduced for 1–3 cm in 57% of the patients after the application of galvanic current, in 89% after modulated current and in 83% after interferrent current. Physicians evaluated the effect of the electric therapy with the mean grade of 4.2 by patients and with 4.05. Conclusion: Electric therapy has a statistically significant influence in the pain reduction in rheumatoid patients, but there is not a significant difference between them. It is an inexpensive therapy without side effects and it has to be in use more then it was until now.